PROBLEMATIKA GURU DALAM MENERAPKAN KURIKULUM MERDEKA BELAJAR PADA SISWA KELAS V SEKOLAH DASAR WILAYAH KOTA TANGERANG - Jihan Fitri Tsabitah; Ina Magdalena; Rizki Zuliani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Curriculum changes in elementary schools always bring new stories for teachers who stand at the frontline of learning. In the implementation of the Merdeka Curriculum, grade V teachers encounter challenges that arise not only from within themselves but also from the school environment. Through observation, interviews, and documentation, a clear picture emerges of the issues they face. Internally, teachers often struggle with designing learning tools such as Learning Objective Flow (ATP) and teaching modules, as well as finding suitable teaching methods that meet students’ needs. Externally, the limitations are visible in the lack of learning media, insufficient school facilities, and various obstacles in carrying out the Pancasila Student Profile Strengthening Project (P5). Despite these barriers, efforts for improvement are continuously made through collaboration among teachers, creative use of simple media, and support from school leaders. These findings highlight that the implementation of the Merdeka Curriculum is still in an adaptation phase, requiring time, strategies, and the involvement of all stakeholders. Consistent support from schools, parents, and policymakers is essential so that the spirit of independent learning can truly be experienced by students in the classroom.